Designing a Cloud Based Assessment Model: A New Zealand Polytechnic Case Study - Rickards, Anthony; Steele, A. (IGI Global, 2015)
A cloud based assessment learning environment exists when the collaborative sharing features of cloud computing tools (e.g. Google Docs) are utilised for a continuous assessment of student learning activity over an extended period of time. This chapter describes a New Zealand Polytechnic based success story which utilised a multi-method approach to investigate student perceptions of a cloud assessment learning environment. The learning environment factors that are examined in this chapter include progress monitoring, cloud tools (i.e. Google Docs), feedback, cloud storage, technology preference, student achievement, and student engagement. This chapter not only describes this unique learning environment, it also provides a clear insight into student perceptions of the cloud assessment learning environment. In concluding, the chapter provides some outcomes that may be utilised to improve pedagogy and student outcomes in a STEM based multimedia learning environment.